2019
DOI: 10.1016/j.ogla.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Angiographic Outflow Improvement after Trabecular Microbypass in Glaucoma Patients

Abstract: Purpose: To study changes in aqueous humor outflow (AHO) patterns after trabecular micro-bypass (TMB) in glaucoma patients using intraoperative sequential aqueous angiography. Design: Prospective comparative case series Subjects: Fifteen subjects (14 with glaucoma and 1 normal) Methods: Sequential aqueous angiography (Spectralis HRA+OCT; Heidelberg Engineering) was performed on fourteen glaucoma patients undergoing routine TMB (iStent Inject; Glaukos Corporation) and cataract surgery and one normal patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 32 publications
3
55
0
Order By: Relevance
“…However, eyes were used very soon after death (within 4 hours). Previous publications using AA in postmortem human eyes36,65 showed similar results to eyes from living human subjects 39,66,67. AA in feline eyes in vivo can also be performed in the future to address these concerns as well.…”
Section: Discussionmentioning
confidence: 53%
“…However, eyes were used very soon after death (within 4 hours). Previous publications using AA in postmortem human eyes36,65 showed similar results to eyes from living human subjects 39,66,67. AA in feline eyes in vivo can also be performed in the future to address these concerns as well.…”
Section: Discussionmentioning
confidence: 53%
“…The two-stent, multidirectional design of the iStent inject is backed up by robust research in aqueous angiography and computational fluid dynamics (CFD), the most powerful tool available to assess size and flow. In a study by Huang et al, significant aqueous angiographic outflow improvement resulted after iStent inject implantation with cataract surgery [52]. The findings showed reactivation of formerly dormant outflow areas and possible access to up to 6 clock hours of collector channels for aqueous humor outflow.…”
Section: Discussionmentioning
confidence: 97%
“…The CFD models estimated that a single stent (either iStent or iStent inject) was completely capable of conducting all 2.5 μL/ min of aqueous humor production [47]. Huang et al confirmed these findings in an aqueous angiography study of patients undergoing iStent inject implantation with cataract surgery, showing that aqueous outflow patterns improved and formerly dormant outflow areas were reactivated, thereby increasing the span of collector channels for outflow [50].…”
Section: Discussionmentioning
confidence: 99%